EFFECT OF AUTOGENIC TRAINING ON BULLYING-INDUCED ANXIETY IN CHILDREN - Milinia, Straerla Atby; Argaheni, S.ST., M.Keb., Niken Bayu; Perestroika, Grhasta Dian; Novika, Revi Gama Hatta; Nurinasari, Hafi (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: Bullying remains a common issue in character education at Islamic boarding schools, often manifesting in verbal and physical forms. Such experiences can cause significant anxiety in victims. One therapeutic option to address this is autogenic training, a relaxation technique aimed at reducing anxiety levels. Purpose: To determine the effect of autogenic training on reducing anxiety caused by bullying among students at Al-Ukhuwah Islamic Boarding School Sukoharjo, Central Java, Indonesia. Methods: This study employed a pre-experimental one-group pretest-posttest design involving 109 female students in grade VII, selected through total sampling. Participants completed the Olweus Bully Victim Questionnaire (OBVQ) and the Depression Anxiety Stress Scale (DASS-42) before the intervention. The autogenic training was conducted in 15-minute sessions, three times over three weeks. After the intervention, participants retook the DASS-42. Data were analyzed using the Wilcoxon test. Results: The Wilcoxon test showed a significant reduction in anxiety levels after autogenic training (p = 0.001). Before the intervention, most participants experienced severe to very severe anxiety; after the intervention, anxiety levels shifted to moderate and severe. Conclusion: Autogenic training effectively reduces anxiety among students who experience bullying. It is recommended as a supportive method to address students' mental health concerns in educational settings.